2001
DOI: 10.1002/oa.574
|View full text |Cite
|
Sign up to set email alerts
|

DISH and the monastic way of life

Abstract: Diffuse idiopathic skeletal hyperostosis (DISH) is a common condition and its prevalence increases markedly with age. This paper describes the pathology and aetiology of the condition; DISH seems to be related to obesity and type II diabetes and is probably a multisystem hormonal disorder. DISH occurs frequently in human skeletal remains, particularly in those recovered from monastic sites. Evidence is presented to confirm this association and the causes are discussed. We also present criteria for the diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
122
1
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(133 citation statements)
references
References 41 publications
0
122
1
7
Order By: Relevance
“…The changes observed in Cosimo I and Ferdinand I meet the standard major criteria established for the diagnosis of DISH [17]. Both skeletons show ossification of the right anterior ligament of the column with the involvement of at least three vertebrae in Cosimo and, in the case of Ferdinand, even of seven vertebrae, and also diffuse ossification of many articular ligaments and entheses.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The changes observed in Cosimo I and Ferdinand I meet the standard major criteria established for the diagnosis of DISH [17]. Both skeletons show ossification of the right anterior ligament of the column with the involvement of at least three vertebrae in Cosimo and, in the case of Ferdinand, even of seven vertebrae, and also diffuse ossification of many articular ligaments and entheses.…”
Section: Discussionmentioning
confidence: 59%
“…In the cemetery of Wells Cathedral and Royal Mint in London a statistically significant difference was observed between the priests' and lay-benefactors' burials in the churches and chapels, which showed higher values, and those of the general population in the ''normal'' cemeteries [17]. The authors explain this variation mainly due to occupational factors and differences in food access.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Classic features such as flowing ossification on contiguous vertebral bodies (blocks of two and six vertebrae) and preservation of the inter-vertebral disc spaces with the non-involvement of the facet joints are the spinal criteria met here to propose the diagnosis of DISH (Aufderheide and Rodriguez-Martin 1998;Crubézy 1990;Mader 2003;van der Merwe et al 2012;Rogers and Waldron 2001); the sacroiliac joint is also affected at the upper (ligamentous) portion (Dar et al 2007;Olivieri et al 2009;Rogers et al 1985;Cammisa et al 1998;Waldron and Rogers 1990) thus being adopted as pathognomic of the condition. These features are different from those observed in spondyloarthropathy and other joint conditions which are characterized by fusion across the intervertebral spaces, syndesmophytes formation, bilateral sacroilitis, and erosion or fusion of hands and feet (Arriaza 1993;Cawley and Paine 2015;Ortner 2003;Resnick 1976;Rogers et al 1985;Waldron 2009).…”
Section: Discussion Diagnosismentioning
confidence: 99%
“…In the clinical (Cammisa et al 1998;Olivieri et al 2009) and paleopathological (van der Merwe et al, 2012) literature the diagnosis of DISH uses a set of features observed in the spinal and extra-spinal skeleton (Crubézy 1990;Arlet and Maziéres 1985;Resnick and Niwayama 1976;Rogers and Waldron 2001;Utsinger 1985;Waldron 2009). These criteria vary according to the method used; in the present study, the features observed include the ossification of the anterior longitudinal ligament along the anterolateral aspect of at least four continuous vertebral bodies (mainly in the lower thoracic spine), preservation of intervertebral disc spaces, symmetrical extra-spinal osteophytes, and absence of apophyseal joint ankylosis.…”
Section: Skeletal Diagnosis Of Dishmentioning
confidence: 99%